2011
DOI: 10.1038/sj.bjc.6606033
|View full text |Cite
|
Sign up to set email alerts
|

CD9P-1 expression correlates with the metastatic status of lung cancer, and a truncated form of CD9P-1, GS-168AT2, inhibits in vivo tumour growth

Abstract: Background:Loss of CD9 expression has been correlated with a higher motility and metastatic potential of tumour cells originating from different organs. However, the mechanism underlying this loss is not yet understood.Methods:We produced a truncated form of partner 1 of CD9 (CD9P-1), GS-168AT2, and developed a new monoclonal antibody directed towards the latter. We measured the expression of CD9 and CD9P-1 in human lung tumours (hLTs), and monitored the level of CD9 in NCI-H460, in vitro and in vivo, in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 33 publications
4
16
0
Order By: Relevance
“…In contrast to the reported molecular compensations based on overlapping expressions of tetraspanins, our current work demonstrates an association between tetraspanin and non-tetraspanin molecules to regulate their expressions in an inverse manner. This kind of association has been recently reported in the case of CD9 and CD9P-1, in which the expression of CD9P-1 positively correlates with the metastatic status of lung tumor cells [38]. In the present study, we demonstrated that inverse correlation between CD9 and CD26 play a role on CD9-mediated suppression of invasiveness of CD26-positive tumor cells.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast to the reported molecular compensations based on overlapping expressions of tetraspanins, our current work demonstrates an association between tetraspanin and non-tetraspanin molecules to regulate their expressions in an inverse manner. This kind of association has been recently reported in the case of CD9 and CD9P-1, in which the expression of CD9P-1 positively correlates with the metastatic status of lung tumor cells [38]. In the present study, we demonstrated that inverse correlation between CD9 and CD26 play a role on CD9-mediated suppression of invasiveness of CD26-positive tumor cells.…”
Section: Discussionsupporting
confidence: 88%
“…Later on, it has been reported to participate in the tetraspanin web [5961]. Expression of PTGFRN positively correlates with the metastatic status of human lung tumors [62]. However, the function of PTGFR in the metastatic process warrants further studies.…”
Section: Discussionmentioning
confidence: 99%
“…When the tumor size has reached 80-120 mm 3 , the mice were injected with E2 (0.036 mg/ml, purity 98%, Sigma) or fulvestrant (Ful, 0.800 mg/ml, Sigma) subcutaneously twice a week (6 weeks) [ 11 ]. All mice were then sacrificed on day 45, wherein the xenograft tumors were harvested and the tumor weight and size were measured [ 36 ]. Tumor tissues were fixed in 4% paraformaldehyde or frozen with liquid nitrogen and stored at -80° C.…”
Section: Methodsmentioning
confidence: 99%